(untitled) (Community Based Medical Journal, 2022)
A cross-sectional study was conducted to examine the diagnostic outcome of visual inspection with acetic acid (VIA) and liquid based cytology (LBC) and see the association of VIA and LBC with HPV status, between March 2015 and June 2017. A total of 72 women attending the Out-Patient Department (OPD) of Gynaecology (Colposcopy Clinic) of Bangabandhu Sheikh Mujib Medical University (BSMMU) for VIA test participated in the study. All the participants underwent both VIA and LBC procedures first. Then HPV DNA test was done in all the cases by hybrid capture (hc2 High Risk HPA DNA test) from residual LBC samples. Thereafter, biopsies were taken from all the patients for histopathological confirmation. The mean age of the participants was 40.22±12.29 years, (age range 18-72). Cervical lesions of total 36 patients were VIA positive. Among them 2(5.6%) patients were HPV positive and 34(94.4%) were HPV negative. There was no significant association found between VIA positivity and HPV positivity (p>0.05). Based on LBC, ASCUS were found in 4 patients, NILM in 52 patients and LSIL in 2 patients; all were HPV negative. ASC-H were found in 4 cases among them 1(25.0%) was HPV positive and 3(75.0%) were HPV negative. Squamous cell carcinoma was found in 1, which was HPV positive. The association between two groups was statistically significant (p<0.05). We found the sensitivity, specificity, accuracy, positive predictive value and negative predictive value of (VIA), as compared against histopathology, were 75.0%, 40%, 45.8%, 20% and 88.9% respectively, while for liquid based cytology (LBC) those were found 75.0%, 90.6%, 88.9%, 50.0% and 96.6% respectively. Our data suggest that liquid based cytology (LBC) with reflex HPV testing gives better results than conventional screening through VIA test. CBMJ 2021 January: vol. 10 no. 01 P: 18-23